Dynamics of India's Intervention in the Sri Lankan Peace Process (2000-2006) - Weerasinghe, M.M.E.P (My University, 2008)
In the past India has repeatedly expressed much concern about the consequences of Sri Lanka's ethnic conflict for her national security. India has even militarily intervened in Sri Lanka to secure a solution to the conflict in the past. During 2000-2006 however, when the fourth Peace Process was established in Sri Lanka the Indian government showed a reluctance to engage actively-and directly in the Sri Lankan Peace Process. This research examines reasons for India's reluctance to playa direct role in the Peace Process 2000/2006. It explores Indian foreign policy changes towards Sri Lanka and argues that India has changed it's foreign policy towards Sri Lanka, adopting a fusion of 'hard' and 'soft' power strategies. It contends that Indian foreign policy is increasingly governed by Economic policies. The research explores how Indian trade, investment, credit/aid, and tourism in Sri Lanka generate soft power for India while creating a strong dependence of Sri Lanka on the Indian economy creating an asymmetric economic interaction that affords India leverage over many overarching issues that affect Sri Lanka. This research examines this economic relationship and argues that it allows India to influence Sri Lankan politics and polices through indirect means. To illustrate these findings both archival and primary research was conducted. Twenty-two interviews were conducted among three diverse categories; academics, politicians and political advisors and Indian investors to ascertain their views on Indo-Lanka relations and India's foreign policy towards Sri Lanka. The findings are indicative that Indian foreign policy towards the Sri Lankan conflict and Peace Processes have changed in recent years. It shows that Indian foreign policy has evolved from mainly hard power strategies in the 1980- and early 1990s to become a fusion of both hard and soft power strategies with more focus on economic relations, in the late 1990s and 21st century thereby being more holistic and multi-dimensional.